A Study of Figurative Language on Traditional Sikka Songs in 2010-2022 - Constantia, Maria (Journal of English Language Teaching, Literature and Culture, 2023)
The purpose of this research is to present the figurative language used in traditional Sikka songs in 2010-2022, there are 20 songs. There are two research problem related of this research that are what are the figurative languages found on traditional Sikka songs in 2010-2022?, And what are the meanings of figurative language found on traditional Sikka songs in 2010 - 2022?. This research also has two objectives of research that are to identify and analyze figurative language on traditional Sikka songs. The researchers used a qualitative descriptive research design to analyze data because the object is in the form of song lyrics. The theory used was from Keraf (2008), about figurative language. The method used in collecting data related to the subject of this research is documentation and interview. The method used in collecting data related to the subject of this research is documentation and interview, because the researchers collected the data from song lyric and interview the meaning of figurative language in Sikka traditional song. The result shows that there were five figurative languages found on traditional Sikka songs. From the data there were simile, personification, metaphor, eponym, and allusion. It can be indicated that the dominant type of figurative language in the song lyric is simile. As a whole, meaning behind this song tells about the life of the Sikka people, who have always maintained peace and harmony since ancient times. And had a message and hope, in which all Sikka people are able to emulate life as it existed in ancient times. It can be concluded that figurative language has important roles in this song lyric. That is why the song writer used so many figurative languages in the lyric.